KARAKTERISTIK PENDERITA EPILEPSI RAWAT INAP DI RSUP HAJI ADAM MALIK MEDAN TAHUN 2011-2013 - Efrida Sirait; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Abstract Epilepsy is a chronic brain disorder that recurrent seizure. In the world epilepsy have 80%, have alot of in the developing countries. Based on the World Health Organization (WHO) report in 2006, the incidence of epilepsy in Europe and North America ranges from 24- 53 per 100.000 per year. Based on data the Association of Physician Spesialist Nerve (PERDOSSI) patient with active epilepsy in 2012 reached 1,8 million of the total population.This research done to know the chracteristic epilepsy patient who are taken treatment in Haji Adam Malik General Hospital Medan in 2011-2013. Descriptive study with case series followed by statistical analysis. Located in RSUP Haji Adam Malik Medan for Juli-Agustus 2014. The population are 126 and sample are all patient epilepsy who are hospitalized ( total sampling) Epilepsy patient with the highest proportion in the age group 0-11 years (47,6%), male gender (52,5%), Islam (62,7%), not attending school (43,6%), other work ( 77,8%), unmarried status (84,9%), outside Medan (61,9%), family tie ( 92,9%), no head trauma (68,3%), classification of primary generalized seizure (79,4%), seizure frequency 1-3x/days (65,9%), no aura (53,2%), long treatments that take about 6 days and condition that come back for treatment (73,0%). From the result of statistical analysis there were significant differences between age and classification of seizure ( p=0,029), and employment and classification of seizure (p=0,006). There is no significant difference between sex with the classification of seizure ( p= 0,136), and education with classification of seizure (p=0,136). Statistical analysis seizure frequency with classification of seizure and classification of attacks while returning state can not be tested. Recommended to the Haji Adam Malik General Hospital Medan to complete the recording on the card status such as etnic group, and precipating factors. Saving the card status well, because 16,7% of the card unknown. People with epilepsy are expected to obey take medicine as directed by doctor and keep a healthy diet an personal higiene. To communities should be care healtiness, specially children. Keywords : Epilepsy, Patient Characteristic